Transformasi Digital Layanan Kuasa Hukum di Pengadilan Pajak: Studi Kasus Sebelum dan Sesudah Implementasi Sistem Online - Ameliya Silaning Utami; Agus Munandar (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
The latest law enforcement license PER-01/PP/2024 dated April 12, 2024 became one of the momentum of change in the modernization of judicial services, especially the Tax Court as the only judicial institution to handle tax disputes specifically in Indonesia. This is done to improve the quality of administrative services through the implementation of a more effective and efficient system while strengthening legal certainty for service users. The Rule replaces the previous provisions of PER-01/PP/2018 which governs the order of the application of legal authority permission in the Tax Court. The study aims to analyze the implementation of the information system of Legal Power Permit (IKH) before and after digitization. The method used is qualitative analysis by conducting literature studies, reviewing business processes, benefits and constraints on the use of IKH information systems online. The results of the analysis show that the system provides ease of access, improves transparency and efficiency of services that can ultimately improve user satisfaction. Limitations in digital literacy of service users are identified as the main obstacles in the implementation of the system that directly impacts the high rate of return of legal authorization permits due to document inconsistencies. This study has limitations in the form of no scientific study that in-depth discusses the IKH online information system in the Tax Court. The results of this study are expected to help identify problems, encourage information transparency, provide socialization recommendations and training aimed at improving the quality and utilization of the system to the maximum.